ICRF mode conversion efficiency in a two-ion component plasma of a tokamak - Grekov, D.L.; Kasilov, S.V.; Tretjak, K.K. (Вопросы атомной науки и техники, 2011)
Mode conversion of fast magnetosonic wave (FMSW) into a short-wavelength wave is studied in the presence of ion
cyclotron absorption and direct electron damping in a tokamak plasma. In plasmas with two (a majority and a light
minority) ion species, FMSW launched from the low-field side ICRF antenna can convert to a slow mode which runs
towards the minority cyclotron resonance point, if the component of confining filed along the big radius of torus is
sufficiently large. The efficiency of conversion has been studied with the help of one-dimensional code which computes
full-wave solution of Maxwell equations with cold plasma conductivity. The dependencies of conversion efficiency on
plasma density and minority concentration have been established. Досліджено конверсію швидкої магнітозвукової хвилі (ШМЗХ) в повільну хвилю (ПХ) в плазмі токамаку з урахуванням іонного циклотронного поглинання ПХ та поглинання ПХ на електронах. В двокомпонентній плазмі ШМЗХ, що випромінюється з боку слабкого магнітного поля, може трансформуватися у ПХ, яка поширюється в напрямку циклотронного резонансу іонів малої добавки, якщо проекція полоідального магнітного поля в напрямку великого радіуса тора достатньо велика. Ефективність конверсії вивчалась за допомогою одновимірного коду, який розв’язував систему рівнянь Максвелла в наближенні холодної плазми. Отримано залежність ефективності конверсії від концентрації малої добавки та густини плазми. Исследована конверсия быстрой магнитозвуковой волны (БМЗВ) в медленную волну (МВ) в плазме токамака с учетом ионного циклотронного поглощения МВ и затухания МВ на электронах. В двухкомпонентной плазме БМЗВ, излучаемая со стороны слабого магнитного поля, может трансформироваться в МВ, которая распространяется в направлении циклотронного резонанса ионов малой добавки, если проекция полоидального магнитного поля на направление большого радиуса тора достаточно велика. Эффективность конверсии изучалась с помощью одномерного кода, который решал систему уравнений Максвелла в приближении холодной плазмы. Получена зависимость эффективности конверсии от концентрации малой добавки и плотности плазмы.